Influence of different hydrocolloids on dispersion of sweet basil seeds (Ocimum basilicum) in fruit-flavoured beverages - Prabhuswamy, Thanushree (Array, 2019)
Sweet basil seeds (Ocimum basilicum) are a rich source of dietary fiber. Considering the importance of dietary fiber on human health and the rising market demand for functional beverages, an attempt was made to develop fruit-flavoured beverages with basil seeds suspension. Different hydrocolloids like carrageenan, xanthan gum, gelatin and gum arabic were used at 0.02, 0.3, 1 and 2% w/v, respectively, to understand the stability of dispersed sweet basil seeds in fruit-flavoured beverages. The developed beverage samples were analyzed for colour (L*, a*, b*), zeta potential (Z), viscosity and relevant organoleptic qualities. Results showed that beverage composition with xanthan gum had Z value of -34.1 mV and viscosity of 232.6 cP, provided better stability for the dispersion of basil seeds. The hydrocolloids gelatin and xanthan gum showed a slight variation in colour values. Beverages containing 0.3% w/v xanthan gum were found to be the best formulation for the production of fruit-flavoured beverages with uniformly suspended basil seeds.